من الحداثة إلى ما بعد الحداثة - مقورة, جلول (University of Eloued جامعة الوادي, 2018)
لم يتوقف الفكر الغربي منذ عصر التنوير إلى الآن عن مساءلة أساليبه، ومقوماته، الأمر الذي أفضى إلى أن يكون النقد طريقه الأوحد. ومنذ إرهاصات الحداثة الفكرية، والحداثة لم تكف عن محاسبة نتائجها، ويبدو أن سؤال الحداثة تم حصرياً، داخل المنظومة الفكرية الغربية، حتى أصبح مفهوماً لصيقا بالغرب. فإلى أي مدى يصدق هذا التلازم بين الحداثة والغرب؟ وهل يمكن وضع تعريف محدد للحداثة؟ أم أن مفهومها زئبقي يتأرجح بين أسسها الفلسفية التي أنشأتها حيناً، والخصائص والمميزات التي رافقتها، والنتائج التي أفضت إليها أحايين أخرى؟ From modernity to postmodernism Abstract : Western thought has not ceased since the Enlightenment until now to question its methods and its components, which led to criticism being the only way. Since modernity, intellectual and modernity has not stopped accounting for its results, and it seems that the question of modernity was exclusively within the Western intellectual system, until it became a concept of the West. How true is this correlation between modernity and the West? Can a specific definition of modernity be developed? Or is its concept mercurial oscillating between the philosophical foundations created by the time, and the characteristics and characteristics that accompanied it, and the results that led to other times
From modernity to postmodernism
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 04 جامعة الوادي
Keywords: الحداثة، ما بعد الحداثة، النقد الفلسفي; modernity, postmodernism, Philosophical Criticism